2012
DOI: 10.26719/2012.18.5.439
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of fetal demise after trauma in pregnant Saudi Arabian women

Abstract: In Saudi Arabia, road traffic crashes are becoming a serious public health problem and there are no recent, large-scale, published reports discussing maternal and fetal injuries. We aimed to explore the predictors of fetal death/abortion after maternal trauma. A retrospective case-control study was performed exploring cases of maternal trauma. The study group included 118 women with pregnancy loss while 308 women without loss represented the control group. All data were compared using univariate analysis follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…7 Al Mulhim et al defined the three most important predictors of poor fetal outcomes or demise as traumas occurring in the second trimester of pregnancy, placental abruption, and a high maternal injury severity score (ISS). 8 Theodorou et al further defined a high ISS as a score of >9 and found it to be a predictor of poor fetal outcome. 9 This study also found that pregnancy of fewer than 23 weeks in conjunction with ISS of >9 increased fetal mortality by 5-fold.…”
Section: Introductionmentioning
confidence: 99%
“…7 Al Mulhim et al defined the three most important predictors of poor fetal outcomes or demise as traumas occurring in the second trimester of pregnancy, placental abruption, and a high maternal injury severity score (ISS). 8 Theodorou et al further defined a high ISS as a score of >9 and found it to be a predictor of poor fetal outcome. 9 This study also found that pregnancy of fewer than 23 weeks in conjunction with ISS of >9 increased fetal mortality by 5-fold.…”
Section: Introductionmentioning
confidence: 99%